Central nervous system involvement in chronic inflammatory demyelinating polyradiculoneuropathy—MRS and DTI study - Dziadkowiak, Edyta; Koszewicz, Magdalena; Podgórski, Przemysław; Wieczorek, Małgorzata; Budrewicz, Sławomir; Zimny, Anna (Frontiers in Neurology, 2024)
Objective The current research aimed to analyze the alterations within the motor cortex and pyramidal pathways and their association with the degree of damage within the peripheral nerve fibers in patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). To achieve that goal, we investigated the microstructural changes within the pyramidal white matter tracts using diffusion tensor imaging (DTI) parameters, evaluated metabolic alterations in both precentral gyri using magnetic resonance spectroscopy (MRS) ratios, and correlated them with the neurographic findings in patients with CIDP. Methods The spectroscopic ratios of NAA/Cr, Cho/Cr, and mI/Cr from both precentral gyri and the values of fractional anisotropy (FA), axial diffusivity (AD), and mean diffusivity (MD) from both of the corticospinal tracts were correlated with the results of neurological and neurographic findings. The comparison of DTI parameters between the patients and controls was performed using Student’s t-test or the Mann–Whitney U test. Due to the lack of normal distribution of most variables, Spearman’s Rho rank coefficient was used to test all correlations. All analyses were performed at a significant level of alpha = 0.05 using STATISTICA 13.3. Results Compared to the control group (CG), the patient group showed significantly lower ratios of NAA/Cr (1.66 ± 0.11 vs. 1.61 ± 0.15; p = 0.022), higher ratios of ml/Cr in the right precentral gyrus (0.57 ± 0.15 vs. 0.61 ± 0.08; p = 0.005), and higher levels of Cho/Cr within the left precentral gyrus (0.83 ± 0.09 vs. 0.88 ± 0.14, p = 0.012). The DTI parameters of MD from the right CST and AD from the right and left CSTs showed a strong positive correlation (0.52–0.53) with the sural sensory nerve action potential (SNAP) latency of the right sural nerve. There were no other significant correlations between other DTI and MRS parameters and neurographic results. Significance In our study, significant metabolic alterations were found in the precentral gyri in patients with CIDP without clinical symptoms of central nervous system involvement. The revealed changes reflected neuronal loss or dysfunction, myelin degradation, and increased gliosis. Our results suggest coexisting CNS damage in these patients and may provide a new insight into the still unknown pathomechanism of CIDP.